IMPROVING ELEMENTARY SCHOOL TEACHERS’ SKILLS IN USING THINK TALK WRITE LEARNING MODEL THROUGH ACADEMIC SUPERVISION - Asnawati; Ary Kiswanto Kenedi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was motivated by the fact that most of the learning processes were not in accordance with the characteristics of elementary school students, which impacted the quality of learning at schools that did not achieve the learning goals. The learning process included planning, implementing, and assessing by the primary school teachers. The purpose of this study was to improve teachers’ skills in carrying out the learning process by using a cooperative model of Think Talk Write type. This research was a school action research adapted from McTaggart and Kemmis's classroom action research design, consisting of stages of planning, implementation, observation, and reflection. The research was carried out at SDN 23 Ujung Gurun Padang, involving 10 teachers. Data were collected using observation sheets to measure the results of the learning process, including planning skills, implementation abilities, and assessment abilities, and analyzed quantitatively. The results showed that the teachers’ average score in carrying out the learning process using the Think Talk Write type cooperative model in cycle I was 68.30, which increased to 85.46 in cycle II. This proved that there was an improvement in teachers’ skills in carrying out the learning process by using the Think Talk Write type cooperative model through academic supervision activities. The implication of this research is that this model can be used as a reference for academic supervisors to improve the quality of learning for elementary school teachers.